2022
DOI: 10.1007/s12072-022-10334-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: effect of adding branched chain amino acids to exercise and standard-of-care on muscle mass in cirrhotic patients with sarcopenia

Abstract: Background The role of branched-chain amino acids (BCAA) in improving muscle mass in cirrhosis is presently debatable. Aims To evaluate the role of BCAA in improving muscle mass in a double-blind randomized placebo-controlled trial in patients with cirrhosis having sarcopenia. Methods Consecutive patients with cirrhosis with Child–Pugh score < 10 and sarcopenia were randomized to receive either 12 g/day of BCAA orally or a placebo (1:1) for 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The search performed in the databases resulted in the selection of studies related to the use of creatine, leucine, branched-chain amino acids, omega 3, and vitamin D. These studies showed that the supplementation with these substances can show benefits in the therapeutic approach of sarcopenic patients. Clinical trials were found only for the use of leucine [20,21], BCAA [22][23][24], omega-3 [25,26], and calcium [27][28][29][30]. These trials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search performed in the databases resulted in the selection of studies related to the use of creatine, leucine, branched-chain amino acids, omega 3, and vitamin D. These studies showed that the supplementation with these substances can show benefits in the therapeutic approach of sarcopenic patients. Clinical trials were found only for the use of leucine [20,21], BCAA [22][23][24], omega-3 [25,26], and calcium [27][28][29][30]. These trials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Much discussion has been raised about the effects of the branched-chain amino acids (BCAA: include valine, leucine, and isoleucine) supplementation as a therapy for sarcopenia, as it encompasses some pathophysiological mechanisms that contribute to the maintenance of lean mass in various pathologies, such as liver cirrhosis, for which, even though there is no consensus on which patients can benefit from supplementation or the ideal amount for each patient, its use is supported [22,95]. In a randomized trial, sarcopenic patients with cirrhosis of the liver were chosen to receive 12 g/day of oral BCAA or placebo for six months, plus 30 min/day of exercise, diet, and standard medical therapy.…”
Section: Branched-chain Amino Acids (Bcaa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is frequent in patients with ESLD; it is observed in >50% of patients with decompensated liver disease and has long been recognized as a determinant prognostic and therapeutic factor [ 92 ]. In patients with cirrhosis and a Child–Pugh score <10 and sarcopenia, supplementation with amino acids for six months did not increase muscle mass relative to PA and dietary advice [ 93 ]. The combination of supplementation with branched-chain amino acids and a home-based exercise program at the anaerobic threshold for 12 months improved aerobic capacity but did not significantly change the body mass index or biochemical markers of liver function [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…From a wider hepatologic perspective, in healthy people in general and in patients with liver cirrhosis specifically, BCAA supplementation promotes anabolic pathways and reduces cachexia, prevents and/or treats hepatic encephalopathy, alleviates fatigue during exercise, promotes wound repair, and stimulates insulin production [ 29 , 30 ]. Going in more detail, hydroxy-beta-methyl butyrate (HMB) is an active metabolite of leucine, with anti-catabolic properties, used in several randomized controlled trials (RCTs) in patients with liver cirrhosis against sarcopenia and fat accumulation in skeletal muscles [ 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%